EFFECTIVE MANAGEMENT OF ONLINE LEARNING DURING PANDEMIC AT SDN 1 TANAH TINGGI - Ina Magdalena; Ayu Wahyuni; Davina Dewi Hartana (PROGRES PENDIDIKAN, 2021)
Effective learning can be defined as learning that succeeds in achieving the learning objectives of students as expected by the teacher. But the Covid-19 epidemic has disrupted the conventional learning process. So a solution is needed to answer these problems. Online learning is an alternative that can solve this problem so this research aim is to describe the effective management of online learning during a pandemic at SD Negeri 01 Tanah Tinggi. This research is descriptive – qualitative research and data collection techniques in this study are participant observation and in-depth interviews. In order to achieve effective learning during pandemics, teachers are required to make good and interesting learning designs. Five indicators of effective learning, namely (1) management of the implementation of learning, (2) communicative processes, (3) student responses, (4) learning activities, and (5) learning outcomes. Students can understand and master IT, and students and teachers can communicate well through Blended Learning.